Childhood shocks, safety nets and cognitive skills: Panel data evidence from rural Ethiopia - Berhane, Guush; Abay, Mehari Hiluf; Woldehanna, Tassew (International Food Policy Research Institute, 2015)
Using child-level panel data from rural areas of Ethiopia, this paper analyzes effects of both economic and non-economic shocks on child cognition skills measured after the early childhood age window.